Promocja usług prozdrowotnych w aptece ogólnodostępnej. Ujęcie prawne i ekonomiczne - Żak, Konrad (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The statutory definition of a pharmacy determines it as a health care facility where authorized persons provide, in particular, pharmaceutical services. The pharmaceutical law system specifies the catalog of pharmacy tasks, the list of pharmaceutical services and the responsibilities of professional staff . However, it does not contain the accuracy of pharmaceutical care and pro-health services. Lack of precise legal regulations in this regard makes it difficult to carry out a basic pharmacy mission, namely public health protection. The pharmacy owner’s authority often has to make risky decisions at the frontier of the law. The unclear and imprecise nature of Polish pharmaceutical law often leads to over-interpretation by pharmaceutical regulators and entails the risk of imposing high financial penalties on pharmacies. This article is intended to indicate the area of health-care activity of a pharmacy, which is not specified in the law, which is the provision of additional services defined in the system of law as “other activities”. On the basis of the analysis of the legal acts and the judgements of the administrative courts, a detailed analysis of the Polish pharmaceutical law system was made as regards the admissibility of the provision of health services in pharmacies. The analysis indicates that there exists the legal gap in the system of Polish pharmaceutical law, liquidation of which nobody cares
Keywords: farmacja; usługi farmaceutyczne; prawo farmaceutyczne